Parathyroid hormone and 25-hydroxyvitamin D concentrations in sick and normal elderly people. Issue 6391 (20th August 1983) - Petersen, M M; Briggs, R S; Ashby, M A; Reid, R I; Hall, M R; Wood, P J; Clayton, B E
Abstract : Serum 25-hydroxyvitamin D and immunoreactive parathyroid hormone concentrations were measured in normal elderly subjects living at home and in sick elderly patients in hospital. Normal old people tended to have high 25-hydroxyvitamin D and low parathyroid hormone concentrations; in the sick elderly this pattern was reversed. The raised serum parathyroid hormone concentrations in the sick elderly were not due to poor renal function and may have been a response to vitamin D deficiency. A high serum parathyroid hormone concentration in an elderly patient must be interpreted in the light of the patient's general health and nutritional state. Caution is needed in diagnosing primary hyperparathyroidism in this age group.